PROTOTYPE SISTEM PINTAR PENGELOLAAN TAMAN BUNGA BERBASIS TEKNOLOGI INTERNET OF THINGS (STUDI KASUS TAMAN KUPU-KUPU GITA PERSADA) - Nama, Gigih Forda; Setia, Harlika Nobra; Komarudin, Muhammad; Muhammad, Meizano Ardhi (Vocational School Diponegoro University, 2020)
Usually the process of watering and monitoring of plants in the Gita Persada Butterfly Park in Lampung Province is carried out using conventional methods, this condition create many problems. The research aims is to create a prototype of flower garden application based on Internet of Things (IoT) technology. An application that can help relieve watering activities and monitoring with automated system developed by protoyping method, that consist of; communication stage, quick plan and modelling quick design, construction of prototype, and deployment delivery and feedback. This application use microcontroller Arduino Uno as the main controller, temperature sensor, air humidity (DHT11), soil humidity, ultrasonic sensorsÂ (HC-SR04) and application on smartphones android for monitoring. Data delivery between arduino devices, smartphones and databases using website service. There is a firebase library on website Service to connect to firebase. Data transmitted by the device arduino through the protocol http with the command get, send, and push, then received by website Service and forward to be saved on firebase. Based on the data obtained at the air temperature and humidity monitoring around the smart garden for 31 days from April 8 to May 8 , the lowest air temperature is 25Â°C at 08.00 WIB, 26 April and the highest air temperature 30 Â°C at 12.00 WIB, 19 April. The average air humidity value is at 95%.